O caráter educativo do serviço social do comércio. - Nascimento, Adielma Lima do (2006)
In this work it is argued the relation enters the educative character of the Social Service of the Commerce and the orientações of the politics for control of the work force, as well as the consequences of the assimilation of these orientações for the diligent classroom. For the development of this research, it was used as metodológico resource the bibliographical research and the documentary one. The description-critical perspective was the used theoretical referencial for the accomplishment of the research and the exposition of the studied object. It is defended thesis of that the SESC would have as objective to contribute for the capitalist economic development, guaranteeing way social rendering of services the maintenance and the social control on the diligent classroom of the commerce. Desvelamos that the educative assistance given by the SESC contributes to keep a force of work psicossocialmente adjusted to the period of training of development of the international capital. It is considered that this educative action if inserts in a set of actions directed toward the maintenance of the hegemony of the capital, articulated with the strategies of efetivação of private social politics to reduce the paper and the participation of the State in offers of social services, by means of the implementation of projects and/or programs that focus and direct the criminal actions, at the same time that they promote solidarity between the capital and the work, beyond explicitarem the institutionalization of the profession in the social division and technique of the work. As the educative function of the profession if it transforms and redimensiona before the occured changes in the historical processes of organization reorganization of the production and the work, was looked to show the pedagogical profiles of the Social Service in the process of organization of the culture in the capitalist society. Standing out as the function of social control of the diligent classroom, for the Social Service, it according to acquires pedagogical profiles differentiated changes in the productive process. In this direction, this research intended to desvelar that the educative character of the SESC if translates the formation of a subjectivity of the diligent classroom that is not summarized to the assent or the adhesion to the hegemonic order of the capital, but is associated basically with the acceptance of the capitalism as only horizon of the men, rationality above of the classroom interests and, consequently, that it denies the work as formador of sociabilities and the historicidade of the man.